2018
DOI: 10.1155/2018/9354296
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of the Antioxidant Activity and Protective Action of the Seaweed Gracilaria birdiae

Abstract: The red seaweed Gracilaria birdiae (GB) is farmed and used as food in northeast Brazil. However, the economic potential of this seaweed has been explored little. To enable direct consumption and/or product diversification from GB, it is necessary to evaluate its effect in vivo. In this study, the food of mice was improved with the addition of GB. After 21 days, the consumption of seaweed reduced the weight gain and blood glucose levels in mice. In addition, it increased the trolox equivalent antioxidant capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…A diet rich in fucoxanthin, which is present in edible brown seaweeds such as Eisenia bicyclis and Undaria pinnatifida , could significantly reverse the white adipose tissue weight gain in fat mice and ameliorate blood glucose levels [290]. Similar results were reported for sulfated polysaccharides present in red seaweeds Gracilaria birdiae and Plocamium telfairiae , mainly due to their ability to decrease the rate of differentiation of 3T3-L1 cells into adipocytes [291,292]. Supplementation by the aqueous extract of the green seaweed Ulva lactuca rich in sulfated polysaccharide was effective in attenuating lipid peroxidation process and therefore decreasing TG, LDL, and VLDL and increasing HDL [293].…”
Section: Seaweeds Bioactive Effects: From Pre-clinical To Clinicalmentioning
confidence: 71%
“…A diet rich in fucoxanthin, which is present in edible brown seaweeds such as Eisenia bicyclis and Undaria pinnatifida , could significantly reverse the white adipose tissue weight gain in fat mice and ameliorate blood glucose levels [290]. Similar results were reported for sulfated polysaccharides present in red seaweeds Gracilaria birdiae and Plocamium telfairiae , mainly due to their ability to decrease the rate of differentiation of 3T3-L1 cells into adipocytes [291,292]. Supplementation by the aqueous extract of the green seaweed Ulva lactuca rich in sulfated polysaccharide was effective in attenuating lipid peroxidation process and therefore decreasing TG, LDL, and VLDL and increasing HDL [293].…”
Section: Seaweeds Bioactive Effects: From Pre-clinical To Clinicalmentioning
confidence: 71%
“…After 21 days, the consumption of seaweed reduced the body weight gain and blood glucose levels in mice. In addition, it increased the Trolox equivalent antioxidant capacity, glutathione reductase, and catalase levels compared to those of the control group [3], which indicated that the oxidative stress of the animals was reduced due to the consumption of seaweed. Several papers have shown that seaweeds are also good sources of various bioactive compounds, many of which have a pharmaceutical potential [4,5].…”
Section: Introductionmentioning
confidence: 84%
“…Compared with the MC group, the number and scale of fat vacuoles in the polysaccharide treatment groups (A‐Pro, S‐Pro, and H‐Pro) were reduced. A‐SSCP was the most effective polysaccharide, yielding an approximately normal hepatic appearance with well‐preserved cytoplasm, obvious cell boundaries, with legible nuclei and nucleoli (Barros et al., 2018 ; Chidambaram & Carani Venkatraman, 2010 ; Tian et al., 2012 ). These histopathological results, combined with the antioxidant assays and biochemical tests, suggest that A‐SSCP can protect liver tissue from CCl 4 ‐induced hepatic damage.…”
Section: Resultsmentioning
confidence: 99%